EFEKTIVITAS KEBIJAKAN MAL PELAYANAN PUBLIK TERPADU DI KABUPATEN BARRU - Mumayyisah, Fadiyah; Malik, Ihyani; Riskasari, Riskasari (Universitas Muhammadiyah Makassar, 2024)
This study aims to determine the extent to which the effectiveness of the Integrated Public Service Mall policy in Barru District on the aspects of Goal Attainment, Integration, The type of research used is a qualitative research method. descriptive research type. The data collection techniques used were observation, interviews and documentation. Based on the results of the research, it can be seen from several indicators of policy effectiveness which include: (1) Achievement of objectives has not been optimal because there are still parties or people who have not felt the convenience of this policy (2) Integration, outreach carried out by the Barru Public Service Mall only through social media not yet thoroughly so that the community still feels less informed about the Public Service Mall (3) Adaptation, human resources at MPP Barru can be said to be quite good in terms of skills and abilities in providing services, and facilities the infrastructure at MPP Barru is complete which helps the service process properly